PENGARUH MEDIA PEMBELAJARAN QUIET BOOK TERHADAP PEMBELAJARAN TEMATIK DI KELAS III SD TEMA TEKNOLOGI TRANSPORTASI DI SD NEGERI 104214 KEDAI DURIAN DELI TUA - Ashra Namira Lubis; Putri Juwita (Jurnal Cakrawala Ilmiah, 2025)
This thesis discusses the influence of using Quiet Book media to improve student learning outcomes on learning the theme of Transportation Technology Development in grade III SD Negeri 104214 Kedai Durian Deli Tua. The purpose of this study was to determine the influence of Quiet Book learning media on learning the theme of Transportation Technology in grade III SD Negeri 104214 Kedai Durian Deli Tua. This type of research is Quasi Experiment Design. The subjects of this study were grade III students at SD Negeri 104214 Kedai Durian Deli Tua. This study used John Elliot's design, while data collection was carried out by observation, test and documentation techniques. The results of this study show that the use of Quiet Book media can improve student learning outcomes in the learning process. The improvement of student learning outcomes can be measured from the posttest results that have been done by students. The calculation results obtained by the posttest tcount = 4.35 and ttabel = 2.04, mean tcalculate > ttable which concludes that Ha is accepted and Ho is rejected which is the influence of learning media using quiet books on student thematic learning outcomes. This the results of research at grade III SD Negeri 104214 Kedai Durian Deli Tua have been well achieved